Invasive Fungal Rhinosinusitis. (16th February 2013) - Monroe, Marcus M.; McLean, Max; Sautter, Nathan; Wax, Mark K.; Andersen, Peter E.; Smith, Timothy L.; Gross, Neil D.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Document a 15‐year experience with 29 cases of acute invasive fungal rhinosinusitis (AIFR) and evaluate factors predictive of disease clearance and overall survival. Study Design Case series with chart review. Methods Patients were identified by review of department billing records between 1995 and 2010. Medical records were reviewed for patient demographics, disease characteristics, clinical course including surgical and medical therapy, treatment outcomes, and long‐term survival. Results Twenty‐nine patients with AIFR were identified. Causes of immunosuppression included hematologic malignancy (n=16), diabetes (n=12), medication (n=10), and acquired immunodeficiency syndrome (n=1), with 10 patients having multiple causes of immunosuppression. Facial pain, swelling and orbital symptoms were the most common presenting symptoms. Fungal organisms included Mucor (n=18) and Aspergillus (n=10) species, with one patient infected with both. Disease‐specific survival (DSS) from AIFR was 57%. Intracranial (P=.01) and ethmoid sinus (P=.05) involvement were significantly linked with short‐term disease‐related mortality. Overall survival (OS) at 6 months was 18%. For OS, intracranial involvement (hazard ratio [HR], 4.47; 95% confidence interval [CI], 1.51–13.22) and cranial neuropathy at presentation (HR, 3.2; 95% CI, 1.3–8.2) were significantly associated with shortened survival. Of the five patients surviving >6 months, two developed long‐term major sinonasal complications. Conclusions DSS and OS remain low for patients with AIFR. Extensive surgical resection in patients with these poor prognostic signs should be considered carefully in light of their poor survival. Long‐term survivors are at significant risk of sinonasal complications and should be followed closely. Level of Evidence 4. Laryngoscope, 2012